A detailed view on the rebar–to–concrete interaction based on refined measurement techniques. (1st January 2021) - Cantone, Raffaele; Fernández Ruiz, Miguel; Muttoni, Aurelio
Highlights: Detailed concrete and rebar surface measurements are presented. Rebar-to-concrete interaction analysis based on these measurements. Influence of compatibility of deformations on rebar-to-concrete interaction. New perspective on bond and implications on phenomena related to brittle failures. Abstract: Simplified assumptions have traditionally been made on the rebar–to–concrete interaction in structural concrete to calculate the stress state in rebars. Such assumptions typically consider a uniform stress state in the reinforcement at a given cross section, neglecting compatibility of deformations due to bending of the bar. Such simplifications are fully justified due to the relatively ductile behaviour of the reinforcement. When the ductility is however not sufficient, as for instance in case of fatigue effects in metallic reinforcement or in case of brittle non–metallic reinforcement, corrections have in many cases been proposed on an empirical base. A step forward in the understanding of these latter cases requires a detailed insight of the mechanisms of transfer of forces and the actual strain state of embedded reinforcement, which has not been possible in the past due to limitations in measurement systems. Within this frame, this paper revisits the results of classical tests on bond, tension and bending with the insight provided by detailed measurements on the rebars. On the basis of Fibre–Optic Measurements (FOM) performed along the length of a bar and at different locations, the results show the complexity of the actual interactions between the reinforcement and the surrounding concrete as well as the influence of compatibility of deformations on their response. The results provide a new perspective on the rebar–to–concrete interaction and show its implications on a series of phenomena related to brittle failure modes.